PENGARUH PENGETAHUAN KEWIRAUSAHAAN DAN MOTIVASI BERWIRAUSAHA TERHADAP MINAT PESERTA WIRAUSAHA PADA DINAS KOPERASI DAN USAHA MIKRO KOTA DEPOK - Larasati Aulya Putri (CV. ALIM'SPUBLISHING, 2023)
This study is motivated by the influence of entrepreneurial knowledge and entrepreneurial motivation on the interest of entrepreneurial participants at the Depok City Cooperative and Micro Business Office. This is done to see how much the level of entrepreneurial knowledge and entrepreneurial motivation of entrepreneurial participants in Depok City. The research method used is quantitative method because it is a method used to determine the relationship or influence between two or more variables. Data collection techniques through observation, documentation, interviews and questionnaires distributed to 80 respondents using probability sampling techniques with simple random sampling. In analyzing the data, using Instrument Test, Classical Assumption Test and Hypothesis Test. The results showed that the coefficient of determination was 0.806, this means that 80.6% of the contribution of the Entrepreneurship Knowledge Variable (X1) and Entrepreneurial Motivation (X2) influenced the interest of entrepreneurial participants (Y). The conclusion from the data analysis above is that there is a positive and significant influence of Entrepreneurial Knowledge and Entrepreneurial Motivation on the Interest of Entrepreneurial Participants at the Depok City Cooperative and Micro Business Office.